Applied electromagnetics in materials : proceedings of the first international symposium, Tokyo, 3-5 October 1988 - Miya, K. (Keiichiro), 1919- (Pergamon Press, 1989)
The proceedings of this International Symposium focus on recent advances and current research in the study of electromagnetic phenomena in advanced materials, and the potential applications of such research in a variety of areas, including non-destructive testing, steel-making, and nuclear and electrical engineering. Also discussed is the effect of electromagnetic fields on the micro- and macromechanics of solid materials, and the application of electromagnetics to the preparation and characterization of new superconducting materials. This is a valuable account of current research in an incr.